Screening bile salt hydrolase activity of Lactobacillus isolated from Vietnamese human origins - Tran, Xuan Thach; Vu, Thi Hien; Thu Ha, Thi; Hoa Nguyen, Thi; Hung Hoang, The; Hoang Le, Duc; Van Dong, Quyen; Trung Nguyen, Nam; Nguyen, Thi Tuyet Nhung (Vietnam Journal of Biotechnology, 2022)
Hypercholesterolemia is a major cause of cholesterol build-up in the coronary arteries, which can subsequently lead to heart disease or atherosclerosis. Cholesterol levels can be lowered by cholesterol-lowering drugs but some of these drugs may have harmful side effects, while supplementation of Lactobacillus has shown the potential to reduce serum cholesterol levels by virtue of bile salt hydrolase (bsh) activity. In this study, Lactobacillus plantarum VFE-04, L. rhamnosus VFE-08, and L. plantarum VFE-14, had been isolated from Vietnamese healthy adults, were able to deconjugate glycodeoxycholate (GDC) on MRS plates and MRS broth supplemented with GDC. In addition, deconjugating activity of L. plantarum VFE-04, L. rhamnosus VFE-08, and L. plantarum VFE-14 were also found in cell-free extract as expressed by amount of glycine that released in the supernatant. Four bsh genes including bsh1, bsh2, bsh3, and bsh4 have been identified by PCR in these strains. In addition, L. plantarum VFE-04, L. rhamnosus VFE-08, and L. plantarum VFE-14 also showed high ability to resist bile salts and low pH. The results of 16S rRNA gene analyses showed that L. plantarum VFE-04, L. rhamnosus VFE-08, and L. plantarum VFE-14 and had high similarity scores with L. plantarum ZZU 23 (100%), L. rhamnosus JCM 1136 (99%) and L. plantarum S7 (98.65%), respectively. This study suggests that L. plantarum VFE-04, L. rhamnosus VFE-08, and L. plantarum VFE-14 have the potential to be explored as probiotics in the management of hypercholesterolaemia in near future.